Variables Involved in the Planting of Rice in the Rice Husk - Akasaki, J. L. [UNESP]; Silva, E. J. [UNESP]; Sousa, L. C. [UNESP]; Melges, J. L. P. [UNESP]; Tashima, M. M.; Paya, J. (Trans Tech Publications Ltd, 2012)
Rice production in Brazil in 2010 was approximately 12,2 million tons, and to reach that amount several planting techniques were used with different strains of rice in different rice-growing areas. Since Rice Husk Ash (RHA) is the pozzolan of vegetable origin most studied by researchers working in the area of pozzolanic materials, the present paper evaluates the influence that the form of planting, the climate, the soil, the strain of rice and the origin/amount of nitrogen-based fertilizers used in rice cultivation has on the chemical composition and crystallographic properties of RHA. The results obtained in this paper, confirm the importance of carrying out routine chemical analysis and X-Ray diffraction to maintain the quality control of the CCAs produced, because in situations of large-scale production, husks of different origins may be used.
Keywords: Rice Husk; Rice Husk Ash; Chemical Analisys; X-Ray Diffraction